התמודדות עם שדים: הדרך המאגית והדרך הרבנית - הררי יובל (מחשבת ישראל, 2025)
This article explores the differing attitudes toward demons in two corpora produced by the Jews of Babylonia in late antiquity: the Aramaic incantation bowls and the Babylonian Talmud. Both portray demons as destructive agents present in the human environment, responsible for mishaps, illness, and death. The bowls reflect a largely pragmatic approach—erecting barriers to prevent demonic intrusion, expelling them when detected, and, more rarely, deploying them against rivals through harmful sorcery. The Babylonian Talmud, by contrast, offers a far more complex discourse, expressed in practical guidelines and narrative accounts. From these sources emerge four modes of human–demon interaction: separation and protection, limiting demonic harm, subordinating demons to rabbinic authority, and cooperating with them. These modes rest on the rabbinic conviction—and serve to advance it—that all beings, demons included, fall within a divinely ordered moral system, one with clear principles, recognized representatives, and tangible consequences for the organization of worldly life. Thus, the single magical–technical strategy of the bowls is transformed in the Talmud into a multifaceted configuration of power shaped by rabbinic law, belief and authority.